«Sé» e manifestazione. Sul rapporto tra prospettiva metafisica e cosmologica in René Guénon - CORSO, ROBERTO (S&F_scienzaefilosofia.it, 2022)
«Self» and manifestation. On the relationship between Metaphysical and cosmological perspective in René Guénon Starting from a René Guénon’s study about a particular kind of yoga called «layayoga» (i.e. yoga of dissolution), this essay aims to point out Guenon’s interpretation of the relationship that cosmology and cyclic Hindu’s cosmological theory has with «metaphysical» perspective, that is, the relationship between manifested universe and infinity or non-duality of «ultimate reality», which is called in some cases «Self» (ātmā) or «Supreme Self» (Paramātmā). In addition to being a sign of the arising western interest in the hitherto almost unknown tantric traditions, Guenon’s study, represents for its author an opportunity to point out more than just the «theorical» character of what he means by «metaphysical» traditions.